Perlindungan Hukum Bagi Para Pihak Terhadap Terjadinya Sistem Error Pada Penyelenggaraan M-Banking - Noer Alya Indriani (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
A rapidly developing economy cannot be separated from the support of capital provided through banking credit. However, system errors in the operation of M-banking can cause losses for both customers and banks. This study aims to analyze the legal protection for parties against system errors in M-banking operations and the responsibilities that must be met. The research method used is normative legal research with a statutory approach and conceptual approach. The legal sources used include primary and secondary legal sources, collected through literature study and analyzed using descriptive analytical methods. The results of the study indicate that although there are regulations governing the responsibilities of M-banking service providers, legal protection for customers needs to be strengthened, particularly in terms of dispute resolution mechanisms and compensation. This research recommends enhancing system security and consumer education to minimize risks and the establishment of more specific regulations regarding the responsibilities of M-banking providers in dealing with system errors.